PENGARUH PEMBERIAN INFUSA BATANG GELAGAH (Saccharum spontaneum L.) TERHADAP KADAR GLUKOSA DARAH MENCIT PUTIH (Mus musculus L.) JANTAN YANG DIINDUKSI GLUKOSA - Mira Febrina (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2021)
A study on the effect of reeds infusion (Saccharum spontaneum L.) on glucose levels of male white mice (Mus musculus) given glucose load. This study aims to see the effect of reeds infusion (Saccharum spontaneum L.) to blood glucose levels of male white mice (Mus musculus) given glucose load as much as 2g/KgBB. This research used Oral Glucose Tolerance Test (TTGO) method. Animal experiments were divided into 6 groups. The negative control group was given only aquadest, the comparison group was given 2g/KgBB glucose solution, the positive group was given metformin with the dosage of 65mg/KgBB, the treatment group was given reeds infusion (Saccharum spontaneum L.) with concentration 10, 20 and 30 %. After each test animal was given 30 minutes treatment then given glucose 2g/KgBB orally. Then measured blood glucose levels of mice at minute 30-180. Based on the results of testing the infusion of reeds (Saccharum spontaneum L..) showed that the concentrations of 10, 20 and 30% had decreased levels of white mice blood glucose (Mus musculus L.). However, the results of the two way ANOVA assay continued with the Post Hoc Tukey test showed the results obtained that the duration of administration may affect the decrease in blood glucose levels of mice (p <0.05).